Arabic Calligraphy and Patterns: Contemporary calligraphic arabesque - Abdel Baki, Randa (2016)
This presentation focuses on the development of Arabic calligraphic monograms that are translated into multiple interpretations of pattern designs. The process opens up many design solutions that are each unique in their visual language. Through this presentation, I will highlight the progress and work of my typography students at the Lebanese American University in Beirut. I will show the process of the project that culminates in profuse panoply of rich typographic pattern designs. During the project students are exposed to the anatomy of Arabic letters and the different Arabic classifications such as the Naskh, Nasta’alik, Kufi, Thuluth, Diwani. They understand fundamentals of design while keeping in mind the form, the negative and positive spaces and preserving the basic structure of the Arabic letter. At the initial stage of the course, students are required to design an Arabic calligraphic monogram then develop several motifs derived from their respective calligraphic emblem. With the understanding of arabesque pattern systems and the application of a methodical approach they design various patterns. The repetition of these unique motifs concludes in the creation of an infinite surface of patterns. This design work couples together Arabic calligraphy and pattern designs. It exhibits repeated motifs in a system that evokes the creation of a new contemporary calligraphic arabesque. Starting from the simple forms of an Arabic letter to the complex combination of dual letters in a monogram to finally complete a multifaceted visual language of pattern designs, that vary in colors and changes based on the understanding of negative and positive spaces.